THE ROLE OF CREDIT IN REGIONAL ECONOMIC DEVELOPMENT - Eraliev A.A.; Abdugʻapparov Oybek (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article examines the critical role and strategic impact of credit resources on fostering regional economic development and narrowing regional disparities. The author analyzes the mechanisms through which banking and commercial credits stimulate local entrepreneurship, fund infrastructure projects, and attract direct investments to developing territories. By evaluating current credit allocation patterns, the article identifies key structural challenges in regional financing, such as uneven distribution and access barriers for local enterprises.